Effects of probiotics and fibers on markers of nephropathy, inflammation, intestinal barrier dysfunction and endothelial dysfunction in individuals with type 1 diabetes and albuminuria. The ProFOS Study - Stougaard, Elisabeth B.; Tougaard, Ninna Hahn; Sivalingam, Suvanjaa; Hansen, Christian Stevns; Størling, Joachim; Hansen, Tine Willum; Frimodt-Møller, Marie; Steinert, Robert E.; Varasteh, Soheil; Groop, Per-Henrik; Salmenkari, Hanne; Lehto, Markku J.; et al. (Journal of diabetes and its complications, 2024)
To estimate whether a mix of pre- and probiotics would strengthen the gut barrier and protect the kidneys in individuals with type 1 diabetes and albuminuria. Randomized, placebo-controlled, crossover study. Forty-one participants received synbiotic (pre- and probiotics) mix or placebo for 12 weeks with 6 weeks washout. Primary endpoint was change from baseline to end-of-period in UACR. Secondary endpoints were changes in endothelial glycocalyx thickness, inflammatory and intestinal barrier dysfunction markers, glomerular filtration rate (GFR) and ambulatory systolic blood pressure. Thirty-five participants completed the study. Mean age was 58 (SD 10) years, 73 % (n = 30) were male, median UACR was 134 (IQR 63–293) mg/g, estimated GFR was 75 (30) ml/min/1.73m2. There was no significant difference in UACR with a mean relative change (CI 95 %) from baseline to end-of-treatment of −3.0 (−18.4; 15.5) % in the synbiotic group and −12.0 (−29.6; 9.6) % in the placebo group with no significant difference between treatment periods (9.37 (−25.2; 44.0) percentage points; p = 0.60). No significant beneficial difference in the secondary end points was demonstrated. Twelve weeks treatment with synbiotic mix had no effect on UACR or on any of the secondary endpoints in subjects with type 1 diabetes and albuminuria. •There is need for treatment of CKD in type 1 diabetes. Alterations in the gut microbiota is linked to CKD and diabetes.•Can synbiotics be an intervention to prevent development and progression of CKD in type 1 diabetes?•Treatment with synbiotics had no effect on UACR in subjects with type 1 diabetes and albuminuria.•Unfortunately our study could not find support of using synbiotics as additional treatment.